Long‐Term Application of the Crop Water Stress Index in Midwest Agro‐Ecosystems. (1st September 2017) - Dold, Christian; Hatfield, Jerry L.; Prueger, John; Sauer, Tom; Büyükcangaz, Hakan; Rondinelli, Wesley
Abstract : Core Ideas: The crop water stress index was calculated for corn, soybean, and prairie using eddy covariance and canopy temperature. Crop water stress index increased with decreasing volumetric soil water content in tallgrass prairie with net ecosystem production sensitive to water deficits. Crop water stress index in corn and soybean increased at low and high volumetric soil water content demonstrating that carbon assimilation is affected by deficit and excess soil water contents. Corn ( Zea mays L.) and soybean [ Glycine max (L.) Merr.] are predominantly produced in Iowa under rainfed conditions in which the amount and distribution of rainfall, and ambient air temperature, vary substantially among years. Prairie ecosystems also represent a small but significant portion of the landscape in the Midwest, but are subjected to the same variation in rainfall. Quantifying the effect of rainfall variation on ecosystem productivity is required to understand how the absence and the oversupply of water induces plant water stress and affects plant growth. We used the crop water stress index (CWSI) using canopy temperatures obtained from infrared temperature sensors coupled with eddy flux measurements to quantify the impact of water stress on corn, soybean, and prairie net ecosystem production (NEP) in central Iowa from June to August, 2006 through 2015. The relationships between CWSI and NEP, evapotranspiration (ET), and volumetric water content (VWC) were analyzed for these three canopies. Average seasonal CWSI values varied substantially among years and sites, indicating no‐stress and extreme water stress periods. The CWSI significantly increased with decreasing ET and NEP, signaling that water stress adversely affected transpiration and C assimilation. Prairie CWSI was linearly and negatively related to VWC. Corn and soybean CWSI increased with very dry and wet soil moisture regimes, indicating that corn–soybean cropping systems were negatively affected by both the absence and oversupply of water. The CWSI approach quantifies water stress in different agroecosystems to compare the responsiveness of these systems to the dynamics of seasonal rainfall patterns.